2005
DOI: 10.1186/1471-244x-5-45
|View full text |Cite
|
Sign up to set email alerts
|

Rating of personality disorder features in popular movie characters

Abstract: Background: Tools for training professionals in rating personality disorders are few. We present one such tool: rating of fictional persons. However, before ratings of fictional persons can be useful, we need to know whether raters get the same results, when rating fictional characters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The instrument used was The Massachusetts General Hospital Personality Disorders Checklist (MGH PDC). Such instrument has already been used in a prior study for assessing PD characteristics in films 18 . It is a list with 79 items referring to the diagnostic criteria of ten PD, as per DSM-IV-TR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument used was The Massachusetts General Hospital Personality Disorders Checklist (MGH PDC). Such instrument has already been used in a prior study for assessing PD characteristics in films 18 . It is a list with 79 items referring to the diagnostic criteria of ten PD, as per DSM-IV-TR.…”
Section: Methodsmentioning
confidence: 99%
“…The review evidenced studies that discussed the teaching of personality features through movies 18 , the search for clinical profiles of psychopathic characters from the movies 11 , the teaching of psycopathy related concepts through movies 19 , the characteristics and the teaching of psycopathy through female characters on television programs 20 , analysis of a psychopathic character in the cinema 21 , the context of development of behavior disorder and evolution to APD in a Brazilian film 22 , the identification of several disorders in the cinema, among of which APD in foreign films 23 and, finally, the identification of APD in Brazilian films 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The TIPI has good convergent validity with other widely used five-factor model scales (Gosling et al, 2003; Muck, Hell, & Gosling, 2007), and has demonstrated good test-retest reliability (mean r = .72 across traits; Gosling et al, 2003). It has also been shown to have predictive validity in various forms of research (e.g., Chamorro-Premuzic, Bennett & Furnham, 2007; Hesse, Schleiwe, & Thomsen, 2005; Hodson & Costello, 2007; Spieler et al, 2007), and has been translated into German, Dutch, French, Farsi, Italian, Norwegian, Swedish, and Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…All these extensive validation studies have shown that the TIPI has acceptable psychometric properties even across different cultures and languages (Hofmans et al, 2008;Muck et al, 2007;Romero et al, 2012). The TIPI instrument has been used within different contexts of research, such as business and management (Tabaeian et al, 2012), individual and social preferences (Hesse et al, 2005;Livosky et al, 2012), and clinical psychology (Bunevicius et al, 2008). The Cronbach's alphas for the five TIPI scales in the current study were very similar to the findings by Volk et al (2011), Donnellan et al (2006, Ehrhart et al (2009) and Gosling et al (2003).…”
Section: Procedures and Materialsmentioning
confidence: 99%